A18 IMPROVING COMPLIANCE WITH COLONOSCOPY SURVEILLANCE INTERVAL GUIDELINES. (1st March 2018) - Borgaonkar, M; Pace, D; McGrath, J S; Harding, J
Abstract: Background: Research suggests that colonoscopy is over utilized in patients undergoing colorectal cancer (CRC) or adenoma surveillance. Aims: To improve endoscopist compliance with the 2013 Canadian Association of Gastroenterology (CAG) guidelines on CRC surveillance. Methods: In 2014, a trained nurse reviewed a sample of surveillance colonoscopies conducted by each endoscopist at one of five hospitals in Eastern Health (EH) Newfoundland. The endoscopist recommendation for the next surveillance colonoscopy was compared to that of the CAG guidelines based upon the findings and polyp histology. A three-part intervention was undertaken. First, each endoscopist was informed of their own compliance rate and that of the group. Second, a survey was conducted to ascertain how endoscopists decided upon surveillance intervals and barriers to following guidelines. Finally, the group met to discuss the survey results and identify ways to optimize compliance. In 2016, the same nurse determined the endoscopist compliance rate, which was compared to 2014. Only endoscopists who contributed patients to both time periods were included in the analysis. Approximately 25 cases were chosen for each endoscopist at each time point. Data were entered into SPSS version 20.0 for analysis. The study received approval from the local Health Research Ethics Board. Results: In 2014, 526 surveillance colonoscopies performed by 18 endoscopists (10 Surgeons, 8 Gastroenterologists) were reviewed. Surveillance intervals were appropriate in 74.9% of cases. Endoscopist compliance rates ranged from 50.0% to 100%. Fourteen endoscopists completed the survey on guideline compliance. 85.7% indicated they used the CAG guidelines to determine surveillance intervals. The three most common reasons for deviating from guidelines were poor bowel preparation (71.4%), booking the next procedure prior to reviewing polyp histology (50%) and patient preference for a different interval (50%). These results prompted EH to emphasize to patients the importance of high quality bowel preparation and to utilize split dose preparations more frequently. In 2016, 533 surveillance colonoscopies performed by the same endoscopists were reviewed. Surveillance intervals were appropriate in 82.7% of cases (p=0.002 compared to 2014). Endoscopist compliance ranged from 56% to 100%. It was noted that Gastroenterologists had a higher level of compliance than surgeons (84.9% vs. 72.7%; p<0.001). Conclusions: A multi-faceted intervention was associated with an improvement in compliance with the CAG colonoscopy surveillance guidelines. Further study is required to determine which part of the intervention was most effective and if these results are sustained over time. Funding Agencies: Health Care Foundation